(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Cryptococcosis is a frequent complication in immunosuppressed patients, causing mainly central nervous system and lung infection, and leading to increased mortality risk. CASE PRESENTATION We present the first documented case in Switzerland of Cryptococcus gattii pneumonia in a kidney-pancreas transplant patient, with a concomitant Pneumocystis jirovecii infection mimicking an immune reconstitution syndrome. Diagnosis of cryptococcal pneumonia was based on a positive serum cryptococcal antigen and confirmed by Grocott’s methenamine silver and periodic acid-Schiff stains on bronchoalveolar lavage fliud. C. gattii was identified with mass spectrometry and antifungal susceptibility testing by microdilution was performed. After an initial successful treatment with liposomal amphotericin-B, flucytosine and tapering of immunosuppression, the patient clinically deteriorated, developing bilateral diffuse ground-glass opacities with consolidations on chest computed tomography. A diagnosis of probable P. jirovecii pneumonia versus an immune reconstitution syndrome was considered. Because of a high titre of Pneumocystis on polymerase chain-reaction testing of bronchoalveloar lavage fluid and high serum b-D-glucan, a diagnosis of probable P. jirovecii pneumonia was made. CONCLUSION This case illustrates the potential complications of a cryptococcal infection in immunosuppressed hosts, despite timely diagnosis and appropriate antifungal therapy.